Overlap Syndrome: A case with features of both Sturge Weber and klippel trenaunay phacomatoses - Nischala Balakrishna; Seema Channabasappa (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2020)
Background: Sturge Weber and Klippel Trenaunay syndromes are mesodermal phacomatoses occurring sporadically. We report a rare case with overlapping features of both syndromes. Case report: An eight-year-old girl complains of low vision and pain in left eye for nine months. Examination revealed port wine stain on left side of face, fingertips and toes present since birth. Length of both legs was symmetrical with skin hypertrophy. Visual acuity was light perception and lid swelling with hyphema noticed in left eye. BScan showed retinal detachment with choroidal haemangioma. CT scan showed orbital inflammation. The haemangioma was treated with Intravitreal Bevacizumab followed by vitrectomy with subretinal fluid drainage and focal laser. Radiotherapy was given to the left orbit. Conclusion: Nevus flammeus, choroidal haemangioma, retinal detachment and neovascular glaucoma consistent with Sturge Weber syndrome. Soft tissue hypertrophy with dilated veins is compatible with Klippel Trenaunay syndrome.